2015
DOI: 10.1016/j.jvsv.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The European multicenter cohort study on cyanoacrylate embolization of refluxing great saphenous veins

Abstract: Endovenous CA embolization of refluxing GSVs is safe and effective without the use of tumescent anesthesia or compression stockings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 21 publications
(29 reference statements)
4
117
0
11
Order By: Relevance
“…We were enlightened by the new tumescent-free ablation method of a recently published two-year study by Almeida et al [14] with a 92 % closure rate, and of a recently published multi-centre study by Proebstle et al [15] in Europe with a 92.9 % closure rate. In a new comparative study by Morrison et al [16], closure rates were 99 % for cyanoacrylate embolisation compared with 96 % for RFA at three months.…”
Section: Discussionmentioning
confidence: 99%
“…We were enlightened by the new tumescent-free ablation method of a recently published two-year study by Almeida et al [14] with a 92 % closure rate, and of a recently published multi-centre study by Proebstle et al [15] in Europe with a 92.9 % closure rate. In a new comparative study by Morrison et al [16], closure rates were 99 % for cyanoacrylate embolisation compared with 96 % for RFA at three months.…”
Section: Discussionmentioning
confidence: 99%
“…The eSCOPE study showed that CAE is safe and effective in the treatment of GSV incompetence. 54 The VeClose multicenter RCT has demonstrated that CAE is non-inferior to RFA. Among 222 patients with GSV reflux randomly assigned to receive either CAE with VenaSeal or RFA, occlusion rates were 99% for the CAE compared with RFA (96%) at 3 months follow-up.…”
Section: Cyanoacrylate Glue (Ca)mentioning
confidence: 99%
“…Nevertheless, when looking at pain scores during and along the fi rst weeks after the intervention, MOCA outperforms RSTA [57]. Treating refl uxing saphenous veins by cyanoacrylate ablation (CA) is the most recent development in non-tumescent, non-thermal ablation [58,59] which overcomes even some of the limitations of MOCA. While both, MOCA and CA do not cause paraesthesia, in contrast to MOCA, CA is lacking a dose limit, allowing the simultaneous treatment of up to four saphenous veins in the same session.…”
Section: Non-thermal Non-tumescent Ablation Of Saphenous Veinsmentioning
confidence: 99%